Basic Anxiety Dan Basic Hostility Tokoh Rafajar Dalam Novel Stigma Karya Hindhiastinaaa : Kajian Teori Karen Horney - Shafa Rizqia Azharani; Sheva Suci Guevara; Eva Dwi Kurniawan (Universitas Palangka Raya, 2024)
This research aims to describe the vicious cycle, basic anxiety and basic hostility in the character Rafajar in the novel Stigma by Hindhiastinaaa. This research uses a qualitative descriptive type of research. The method used uses a literary psychological approach with Karen Horney's theory of basic anxiety and basic hostility. The aim of this research is to discuss the character Rafajar in the novel Stigma by Hindhiastinaaa. The data taken in the research is in the form of words, sentences, paragraphs, quotes, dialogues related to the symptoms of basic anxiety and basic hostility in the character Rafajar. The data source for this research is the novel Stigma by Hindhiastinaaa, published by Rain Books in 2022. Data collection techniques are reading and note-taking. The results of the research show that the main cause of basic anxiety and basic hostility experienced by the character Rafajar in the novel Stigma by Hindhiastinaa is the lack of love from his parents.